A Study on Drug Utilization Pattern of Metformin and its Different Formulations Used in Patients with Type-2 Diabetes Mellitus in Tertiary Care Teaching Hospital - Dhaval B. Joshi; Jitendra D. Lakhani; Ronak Y. Siddhpuria; Hiral P. Tandel; Nisarg R. Hajariwala (Journal of Integrated Health Sciences)
Background: Drug utilization evaluation is conducted to determine the rational use of drug by describing the drug usage pattern. This study aimed to describe the drug utilization pattern of metformin and its oral formulations. Objectives: The objectives of the study were to identify the prescribing pattern of metformin in fixed-dose combination (FDC), along with adjuvant antidiabetic therapy and it is prescribing in different formulations. Methodology: This is an observational study in which a total of 100 type 2 diabetic patients visited to or admitted in General Medicine Department, Dhiraj General Hospital, Piparia, Vadodara, were included as per our inclusion criteria. Result: Among 100 type 2 diabetic patients, 15 patients received monotherapy and 85 patients received combinational therapy of metformin. Out of 120 FDCs of metformin prescribed in 100 patients, plain (conventional release) formulations were most commonly prescribed (39.17%). Among FDC therapy of metformin, glimepiride + metformin, and glimepiride + pioglitazone + metformin combinations were most commonly found. As an adjuvant therapy with metformin, human analog insulin was most commonly prescribed. The sulfonylureas (SUs) were found to be the most commonly prescribed oral antidiabetic drug class along with metformin (SUs). In this study, we found 49% of the patients receiving metformin with low medication adherence. Conclusion: The practice of metformin monotherapy is limited and it is frequently prescribed in combinations with other antidiabetic agents. We observed an almost equal utilization of different oral formulations of metformin. A low medication adherence with metformin emphasizes the need for appropriate patient counseling and therapeutic interventions.